CULTURAL COMMODIFICATION OF WAYANG TOPENG MALANGAN: A CASE AT PADEPOKAN ASMORO BANGUN, MALANG, EAST JAVA, INDONESIA - Arining Wibowo (ENSAINS JOURNAL, 2020)
Abstract: This article focuses on the distinctive perspective of [cultural] commodification of traditional art “wayang topeng malangan”. The distinctive perspective tries to comprehend the causality of [cultural] commodification and considers the struggle and planning of padepokan Asmoro Bangun. This writing aims to show a particular and significant model of modest scale (small) padepokan located around city and does not, regain popularity as a tourism playground yet. This article was written under the result of interviewing some central figures including the leader of padepokan Asmoro Bangun, Tri Handoyo, Raymond Paays  as an art critics, and Edi Wibowo as a mask crafters. Participate-observation and document analysis were conducted to complete and find alternative data. The result of this research showed that [cultural] commodification can be positive. The causality of [cultural] commodification is caused by the consideration to put the maintenance of wayang topeng malangan as the most vital problem, rather than its change. Keywords: Wayang Topeng (Masked-Puppet), Malang, Cultural Commodification.